Analyzing Errors in Students’ Subtitle Products - Muhammad Khafik; Ikke Dewi Pratama (ELE Reviews: English Language Education Reviews, 2022)
Subtitling has constraints that are different from other types of translation. In the pedagogical field, lecturers in subtitling courses must ensure that the students are aware of the constraints to creating a qualified subtitle. The constraints in subtitling frequently cause errors in the subtitles composed by the students. This article discusses the errors found in students’ subtitle products. The researchers took the subtitles of Miacademy Youtube channel videos composed by EFL students studying in one of the state universities in Central Java, Indonesia. Nine videos of Miacademy and their subtitles were analyzed to find the errors in the subtitles. The results revealed that the most frequent error is errors in spatial parameters, specifically on the excessive number of characters per line. The second most dominant error is the errors in the temporal parameter in which most of the students still found problems in obeying the rules of the maximum duration for either a full two-line or a single-line subtitle. Punctuation and letter case errors result from students’ lack of comprehension in mastering the target text language convention. Error in target text editing mainly occurs due to the too-long subtitles, segmentation that is not syntactically acceptable, the decision to omit or retain the source text, and the occurrence of dialect. Further analysis showed that the students need to practice adjusting their translation with the constraints. Likewise, a subtitling brief must be conducted before the lecturer delivers the task to the students by helping the students analyze the possible problems and solutions when composing the subtitles.